A study on the effects of reference price and pricing on product bundle preferences - Lim, Kang Qi (2014)
This study delves into consumer research in the local context – (1) the effects of an internal and external reference price on utility and (2) the impact of price discounts on the perceived value of a product bundle. We further aim to establish how the relationship between internal or external reference price and utility is moderated by Zumba experience in experiment 1. In experiment 2, value consciousness is used to moderate the relationship between reference price and utility in a product bundle.